In Vivo Ciprofloxacin Release from Hydroxyapatite-Based Bone Implants in Rabbit Tibia: A Preliminary Study. (7th December 2011) - Nayak, Amit Kumar; Bhattacharyya, Ajoy; Sen, Kalyan Kumar
Abstract : The present study deals with the preliminary evaluation of in vivo ciprofloxacin release from HAp-ciprofloxacin bone implants in rabbit tibia. The HAp-ciprofloxacin implants (2 × 2.5 mm) were prepared using various HAp-ciprofloxacin composites synthesized by precipitation technique and 1.5% w/v guar gum as a binder. 5 implants were implanted in artificial cortical bone window at the right proximal tibia of each rabbit. After 3- and 6-day intervals, the rabbits were euthanized. Bone marrow and serum concentrations of ciprofloxacin were determined from the harvested tibia using HPLC method. The results displayed the availability of elevated local antibiotic concentration at the implanted site with the limitation of systemic antibiotic exposure, which can be useful to minimize the risk of systemic toxicity-related side effects. This study is the preliminary investigation of the suitability of in vivo ciprofloxacin release from HAp-ciprofloxacin bone implants in rabbit tibia, after implantation, and these implants can be useful for the treatment of bacterial bone infections like osteomyelitis.